Grape rootstock - scion interactions on shoot growth and cane maturing - Kocsis, L. (International Journal of Horticultural Science, 1999)
Interaction between the rootstock and scion varieties (clones) was examined. Berlandieri x Riparia T. K. 5BB, Berlandieri x Riparia T.5C being the most widely used varieties in Hungary, Fercal, Ruggeri 140 being recently used on special soil conditions ; Georgikon 28 a new established variety and Berlandieri x Riparia T. 8B GK 10 clone were the rootstocks used. The V. vinifera L. varieties were a clone of Italian Riesling and two new hybrids from the same cross population f ( Noble Italian Riesling X Ezerjó) X ( Noble Italian Riesling X Pinot Gris ) }. This study presents the results how the growth habit depends on different scion/stock combinations in the first three years.Shoot growth characters were observed during the initial years after plantation in the vineyard until we got the first yields. Our results did not agree with those of Pospisilova (1977) that the anticipated vigour of shoot growth will appear later in the vineyard only. However we agree with Zimmerman (1970), who showed that the differences are caused by the rootstocks in the growth habit of vines during the first two years already. The differences in shoot elongation decreased similarly to the rootstocks in the first year of fruit production. It shows us that the intense root development caused vigorous shoot growth, which we think to be a rootstock effect. When the vegetative and generative development are balanced already, the effect of scions in shoot elongation became stronger than the effect of rootstock.We also found great differences in the maturation of wood each year from planting of the vineyard to the year of fruit production.During the first years the differences of cane maturation were greater according to the scion varieties, the means were significantly different. In the first ripening year the differences dwindled or increased due to the rootstocks. This means that the effect of the rootstock on cane maturation became stronger in the first year of fruit production.